False-negative diffusion-weighted imaging findings in acute stroke - Otomo, Takashi; Ishikawa, Tatsuya; Matsuda, Hiroshi; Yuasa, Naoki; Takagi, Shigeharu; Shiramizu, Hideki; Kitagawa, Yasuhisa (Japanese Journal of Stroke, 2006)
The utility of DWI (diffusion-weighted imaging) has been established in acute ischemic stroke. However, some patients with acute stroke show no abnormal signals on DWI, despite the presence of infarction (false-negative DWI). We analyzed the relationship between false-negative DWI and the clinical manifestations of acute ischemic stroke in 151 DWI-positive (89%) and 19 false-negative DWI (11%) patients. We performed MRI within 24 hours after onset at our hospital. Non-specific clinical manifestations, including vertigo and nausea, were frequently observed in false-negative DWI patients. As regards the vascular territory, false-negative DWI was noted in 15.3% of 59 patients with infarctions within the territory of the vertebrobasilar artery. Concerning the duration from onset to initial imaging, 73.7% of the patients with false-negative DWI findings underwent MRI examination within 6 hours after onset. Of the patients with false-negative DWI, 84.2% had lacunar infarction (X2=16.4, P<0.001). In conclusion, false negative DWI is more frequently observed in lacunar infarction than in atherothrombotic infarction or cardiogenic embolism. It is important to examine carefully the neurological changes occurring in patients who present with acute stroke, but have negative DWI findings.